2018
DOI: 10.1111/jgs.15694
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Normative MMSE Data for Older Persons Aged 85 to 93 in a Longitudinal Swedish Cohort

Abstract: Background/Objectives Normative Mini‐mental state examination (MMSE) reference values in elderly are scarce. Therefore, the aim is to present normative MMSE values for 85–93 year olds. Design A longitudinal age cohort study. Setting A population study of the residents in the municipality of Linköping, Sweden. Participants Residents (n = 650) born in 1922 during the course of 2007. In total, 374 individuals participated and were tested with MMSE at age 85, 280 of these were willing and able to also participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…The SMMSE is overly weighted towards tests of orientation (one-third of its points), which is best able to identify established dementia [28]. Further, while a cut-off of <24/30 is widely applied for the SMMSE, recent studies suggest that higher cut-offs between 26 [37] and 29 [13], closer to that found here, are more accurate and produce a better balance between sensitivity and specificity. As with its’ original validation study [8,28], this analysis confirms the Q mci screen is more accurate overall and that its logical memory subtest is its most accurate for separating MCI from normal controls.…”
Section: Discussionmentioning
confidence: 67%
“…The SMMSE is overly weighted towards tests of orientation (one-third of its points), which is best able to identify established dementia [28]. Further, while a cut-off of <24/30 is widely applied for the SMMSE, recent studies suggest that higher cut-offs between 26 [37] and 29 [13], closer to that found here, are more accurate and produce a better balance between sensitivity and specificity. As with its’ original validation study [8,28], this analysis confirms the Q mci screen is more accurate overall and that its logical memory subtest is its most accurate for separating MCI from normal controls.…”
Section: Discussionmentioning
confidence: 67%
“…Both young and old participants completed the Mini-Mental State Examination (MMSE 47 ) before taking part in the emotion recognition tasks. A cutoff score of 26 (adapted for Swedish populations 48 ) suggests potential cognitive impairment. All participants scored higher than this cutoff and no participants were excluded based on this criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Scores range from 0 to 30, with a score <24 generally used to raise a suspicion of cognitive impairment [115]. However, very recently a higher MMSE cut-off at ≤26 has been suggested for older persons up to the age of 93 [116]. Consequently, an MMSE cut off of <24 may be a conservative MMSE value to indicate cognitive impairment in these populations.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…MMSE scores range from 0 to 30, with a score below 24 generally used to raise a suspicion of cognitive impairment [115]. Even though the 24 cut-off level has been challenged [116], it can be regarded as a conservative cut-off level with few false positive cases. However, MMSE is a screening test.…”
Section: Cognitive Impairmentmentioning
confidence: 99%